Longer Baseline Left Ventricular Activation Time Is Associated With Lower Mortality and Lower Risk of Heart Failure Hospitalization in Cardiac Resynchronization Therapy Recipients - Marinko, Sofia; Platonov, Pyotr G.; Borgquist, Rasmus ; 0000-0002-1365-6637 (Annals of Noninvasive Electrocardiology, 2026)
Introduction: Many patients do not benefit from cardiac resynchronization therapy (CRT) with current guideline parameters. The objective of this study was to examine the relationship between left ventricular activation time (LVAT) from the standard 12-lead surface electrocardiogram (ECG) and clinical outcome from CRT. Methods: A retrospective study was performed on patients receiving CRT implants at a large-volume tertiary care center. Digital ECGs were collected pre- and post-implant. LVAT was defined as the time from QRS onset to maximum deflection in lead V6. The primary combined endpoint was heart failure hospitalization or all-cause mortality. Results: The study group comprised 415 patients (median age [Q1–Q3] of 72.8 years [65.1–78.7], 77.3% male, median baseline LVEF 27.5% [22–30], and 43.1% with ischemic heart failure etiology) who were followed for up to 7.6 years (median 2.8). LVAT was measured pre-implant (median 78 ms [66–98]) and post-implant (median 88 ms [74–106]). In Kaplan–Meier analysis, a longer pre-implant LVAT was associated with a reduced risk of reaching the primary endpoint in patients with LBBB (log-rank p = 0.046). Post-implant LVAT was not associated with clinical outcome. Conclusion: Our results show that a longer baseline LVAT is associated with a lower risk of heart failure hospitalization and all-cause mortality. This relationship was of borderline significance in multivariable analysis. Prospective trials would be useful to further explore the potential role of pre-implant LVAT in patient selection for CRT.
Keywords: cardiac resynchronization therapy; heart failure; patient selection; prognosis